Minimally invasive abdominal and left thoracic approach for esophagogastric junction adenocarcinoma with esophageal diverticulum: A case report. Issue 2 (11th June 2018) - Takeuchi, Yuta; Ebihara, Yuma; Nakanishi, Yoshitsugu; Asano, Toshimichi; Noji, Takehiro; Kurashima, Yo; Murakami, Soichi; Nakamura, Toru; Tsuchikawa, Takahiro; Okamura, Keisuke; Shichinohe, Toshiaki; Hirano, Satoshi
Abstract: Controversy remains regarding the optimal resection approach for Siewert type II adenocarcinoma of the esophagogastric junction (EGJ). Furthermore, an esophageal diverticulum, although rare, can complicate surgical procedures. Herein, we report a case of EGJ adenocarcinoma with an esophageal diverticulum that was treated using the minimally invasive abdominal and left thoracic approach (MALTA). A 72‐year‐old man, with EGJ adenocarcinoma and an epiphrenic diverticulum on esophagogastroduodenoscopy underwent endoscopic submucosal dissection. The pathological diagnosis of the specimen revealed invasion to the lymphatic vessels. Therefore, laparoscopic proximal gastrectomy and thoracoscopic lower esophagectomy with D1 lymph node dissection and double‐tract reconstruction of the esophageal diverticulum were performed via MALTA. The patient was discharged without any postoperative morbidity. MALTA provides good visualization for the transection of the lower esophagus in cases of esophageal diverticulum. Moreover, MALTA for adenocarcinoma of the EGJ is technically feasible, even with the presence of a lower esophageal diverticulum.